3x+y=2 ----------------------------------------------------(1)
-x+4y=-18--------------------------------------------------(2)
equation(2) x 3 gives equation(3) as
-3x + 12y=-54-----------------------------------------------(3)
3x + y= 2-------------------------------------------------(1)
----------------------------------------------------------------------------
Equation (3) + Equation (1) gives:
13y = -52
Therefore
y = -52 / 13 = -4
Substituting y = -4 into equation (1), we have
3x + (-4) = 2
which implies that
3x = 2+4=6
Thus
x = 6 / 3 =2
The solution as an ordered pair is in the form (x-solution, y-solution)
Hence the solution as an ordered pair is (2, -4)